Hemoglobin Levels in Pulmonary Tuberculosis Patients who Consuming Anti-Tuberculosis Medicine - Supriati Wila Djami; Agustina W Djuma; Marni Tangkelangi (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Tuberculosis (TB) is a lung infection characterized by pulmonary infiltrates and the formation of caseous granulomas, fibrosis, and cavities. TB is the second leading cause of death from infectious diseases worldwide, after the human immunodeficiency virus (HIV). To reduce the death rate due to TB, the government carried out the Find Drugs Until Heal program with examinations for 6-9 months to kill the Mycobacterium tuberculosis bacteria with anti-tuberculosis drugs, namely Isoniazid, Rifampicin, Ethambutanol, Streptomycin, and Pyrazinamide. Anti Tuberculosis Drugs can cause fever, nausea and hematological reactions such as anemia, agranulocytosis, eosinophilia and thrombocytopenia. The research method used is descriptive using a cross sectional approach, namely to find out the description of hemoglobin levels in Tuberculosis patients who consume Anti Tuberculosis Drugs. 60%, in the productive age of 31-50 years with a percentage of 67% and occurs in patients with two months of treatment, namely initial or intensive treatment with a percentage of 87%.